PEMBUATAN ELEKTRODA KARBON DARI BIOMASSA SABUT KELAPA MUDA DENGAN AKTIVATOR KOH SEBAGAI APLIKASI SEL SUPERKAPASITOR - Zurya Hanifa; Awitdrus Awitdrus (Komunikasi Fisika Indonesia, 2022)
The supercapacitor is a storage device consisting of carbon electrodes, separator, electrolyte, and current collector. Carbon electrodes made from young coconut coir biomass with a mass ratio of 1:0.20 KOH activator have been successfully fabricated with a carbonization temperature of 550 °C and a physical activation temperature of 750 °C. Characterization of physical properties by measuring the density value showed that before and after pyrolysis decreased due to KOH activating agent. Furthermore, the electrochemical characterization using the voltammetry cyclic method showed the specific capacitance value to the scanning rate, where the highest specific capacitance value was 163.14 F/g with a scanning rate of 1 mV/s.